2020
DOI: 10.3168/jds.2019-17486
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-specific risk factors in acute outbreaks of respiratory disease in calves

Abstract: Respiratory tract infections (bovine respiratory disease) are a major concern in calf rearing. The objective of this study was to identify pathogen-specific risk factors associated with epidemic respiratory disease in calves. A cross-sectional study was conducted, involving 128 outbreaks (29 dairy, 58 dairy-mixed, and 41 beef) in Belgium (2016Belgium ( -2018. A semiquantitative PCR for 7 respiratory pathogens was done on a pooled nonendoscopic bronchoalveolar lavage sample for each herd. Potential risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 37 publications
9
47
1
1
Order By: Relevance
“…However, cases of infectious keratoconjunctivitis, suppurative otitis media, meningitis, decubital abscesses, endocarditis and reproductive disorders have been associated with M. bovis [ 7 , 8 , 9 , 10 ]. Most importantly M. bovis is one of the causes of BRD with other aetiological agents, both bacterial and viral [ 11 , 12 ].…”
Section: Mycoplasma Bovis : Key Factsmentioning
confidence: 99%
“…However, cases of infectious keratoconjunctivitis, suppurative otitis media, meningitis, decubital abscesses, endocarditis and reproductive disorders have been associated with M. bovis [ 7 , 8 , 9 , 10 ]. Most importantly M. bovis is one of the causes of BRD with other aetiological agents, both bacterial and viral [ 11 , 12 ].…”
Section: Mycoplasma Bovis : Key Factsmentioning
confidence: 99%
“…(32). Also, for the prevalence of M. bovis in the population, prior information was available (7,35). This literature information was combined with the best guesses of experts in the field (first author and senior authors).…”
Section: Diagnostic Test Study (I) Study Population and Sampling Metmentioning
confidence: 99%
“…In available studies, pools of samples from 5 animals were shown to improve diagnostic accuracy at the group level. 36,37 The largest disadvantage of PCR is interpretative difficulty, because PCR can identify dead pathogens, opportunists currently not involved in infection, and contaminants, none of which signify a clinically meaningful test result. This disadvantage was shown, for example, for H somni.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…47 Hence, to improve sensitivity of the group diagnosis, the use of PCR on a pooled sample (up to 5 animals) can be considered. 36,37 A pitfall when working with PCR to detect primary pathogens is that vaccine antigen can be detected up to 14 days after intranasal vaccination with a live vaccine, resulting in false-positives. 48…”
Section: Detection Of Primary Pathogensmentioning
confidence: 99%